CAREGIVERS' STRESS OF CANCER PATIENTS IN A TERTIARY CARE HOSPITAL - Yousafzai, Abdul Wahab; Bhutto, Naila; Ahmar, Syed; Siddiqui, Muhammad Naim; Salamat, Sumera (Journal of Postgraduate Medical Institute, 2011)
Objective: To see psychological stress in caregiver's of cancer patients and also to find out association of stress with demographic variable of caregiver. Material and Methods: This cross sectional study was conducted at oncology department of Aga Khan University Hospital Karachi from July 2006 to December 2006. Sample size was 200 caregivers of cancer patients. General Health Questionnaire 12th version (GHQ-12) was used to measure the mental distress Results: Out of 200 caregivers 166 (83%) were females and among females 56.02% (n=93/166) were house wives. Parents and wives as caregivers constituted 34.5% and 22.5% of the sample respectively. Mean age was 52 years. Mean GHQ score were 11.80. The severity of stress on GHQ-12 scoring were mild (2-4) in 17%, moderate (5-9) in 34% and severe (> 10) in 49 % cases. Patients requiring care at home included patients with blood cancers (40%), gastrointestinal cancer (38.5%) and breast cancers (21%). Mean duration of illness was 3.5 years. Majority of the of patients (65%) were with <1 year and 35% of patients were with > 1 year of duration. Association of stress was significant with female gender (p<0.05), age more than 41 years (p< 0.03), being parent as caregiver (p<0.01) and caring for a patients with illness duration >1 year (p<0.04). Conclusion: Significant number of caregivers has been found to be suffering from severe stress. Age of caregiver, relation with patient, female gender and duration of caregiving were found to be significantly associated with stress.